The Principal's Leadership in Implementing Performance to Improve School Quality - Amelia, Amelia; Siahaan, Amiruddin (Thawalib: Jurnal Kependidikan Islam, 2025)
Although many studies have examined school leadership, few have specifically explored the implementation of leadership in private vocational high schools, particularly regarding performance improvement strategies and their relation to teacher development and educational quality. This study analyzes the principal's leadership in improving school quality through performance enhancement. A qualitative case study method was employed, using observation, interviews, and documentation techniques. Data were analyzed through reduction, presentation, and conclusion drawing, and validated through source triangulation. The results show that the principal of PAB 8 Sampali Private Vocational High School plays a strategic role as a leader, manager, and motivator in enhancing educational quality. He effectively manages resources, implements innovations such as the “Work, Study, Entrepreneurship” program, motivates teachers, and fosters collaboration to create a conducive learning environment. Despite challenges such as policy changes and diverse student characteristics, these were addressed through teacher training and strategic adjustments. His leadership has had a significant positive impact, as evidenced by the school’s accreditation improvement from grade C to A, increased student enrollment, and enhanced achievements. Implementing the Eight National Education Standards has strengthened school quality and fulfilled stakeholder expectations. Conclusion: The principal’s leadership effectively improves educational quality through innovation, sound management, and the ability to adapt to various challenges.